Rules and the doctrine of performance management - Jakobsen, Mads F.; Mortensen, Peter B. (2016)
The doctrine of performance management has been promoted as an alternative to rule-based governance. Analyzing performance management as a system of rules, this article examines how performance management is adopted through rules. The question is examined based on a systematic counting and content coding of national rules within the domain of primary education in Denmark from 1989 to 2010. Contrary to the prescriptions of the performance management doctrine, the analysis shows a clear increase in the number of rules. This reflects the creation of many new rules about performance measurement without a proportionate repeal of production rules constraining the autonomy of public service providers and their managers. The result is congruent with the expectations derived from the literature on rule dynamics, which emphasizes rules as the carriers of learning and interests. The article thereby demonstrates the utility of analyzing performance management as a system of rules. - Reproduced.
Keywords: Performance appraisal